Effectivenes Of Puzzle Play Therapy To Reduce Anxiety, Case Study In Pre-School Age Children Who Undergo Chemotherapy At Rsup Dr. Kariadi Semarang - Sutarmi Sutarmi; Siti Musyarofah; Warijan Warijan; Tavip Indrayana; Joni Siswanto (Jurnal Studi Keperawatan, 2023)
ABSTRACTBackground: Children with cancer will undergo various treatments and the most common is chemotherapy. Chemotherapy and repeated hospitalization make children uncooperative with health workers and anxious. One of the cooperative and collaborative efforts that can be done to overcome children's anxiety is by playing puzzle therapy. Purpose: Knowing the effect of the application of puzzle play therapy on reducing anxiety in preschool children (3-6 years) undergoing chemotherapy during hospitalization. Methods: Case study design based on inclusion and exclusion criteria. The number of respondents was 3 clients. Observation using the instrument of measuring the level of anxiety Preschool Anxiety Scale Revised (PASR). The intervention was carried out for 10-15 minutes 1 hour before chemotherapy. Discussion: There were 3 respondents aged 3-6 years, most of them were women who did not receive chemotherapy for the first time. 2 out of 3 clients experienced severe anxiety and 1 client experienced moderate anxiety, the child seemed to cry, was silent, avoided eye contact, looked tense. After the puzzle play therapy intervention, 2 clients experienced moderate anxiety and 1 client experienced mild anxiety, the three clients seemed calm, didn’t cry, tensed less. Recommendation: In this case study the application of puzzle play therapy can reduce the anxiety level of preschool children undergoing chemotherapy with hospitalization. It is hoped that by carrying out this case study, it can add insight, references, and innovations in non-pharmacological actions for preschool children who are undergoing chemotherapy with anxiety.Keywords: anxiety level; pre-school; chemotherapy; hospitalization; puzzle play therapy.